Diferencial salarial inter-regional no Brasil - decompondo os determinantes do diferencial salarial entre os municípios de Betim e São Bernardo do Campo - Guilherme Marques Moura (2017)
The present dissertation aims to make a comparison in the Brazilian intra-regional salary distribution and its determinants. The main goal is to quantify and analyze if the income inequality existing between the cities of Betim and São Bernardo do Campo are found only intrasetorially or express a salary difference between those regions. Therefore, this work tries to find, point and quantify the regional influence within the income of workers. In this sense, it is adopted the basic hypothesis which claims that the differentiated composition of the labor force between the localities themselves is not able to explain the entire interregional wage differentials. It is believed that this wage difference can be a reflection of the productive structure, local labor markets, regional economic dynamism, cost of living, local amenities, interregional differences in the allocation of human capital, among others. Broadly speaking, the close relationship between the demographic dynamic of the regional labor markets and the spatial structure of economic activities is considerable. For this reason, it is useful to analyze cities as the product of an equilibrium, dynamic or static, where the agglomeration and deagglomeration forces are counterbalanced. Thus, it is necessary to analyze connections between intersectoral relations and regional development, that is, to understand the dynamics of cities. Therefore, it was proposed to analyze the automobile industry within the two urban centers, Betim and São Bernardo do Campo, whose regions have some relative specialization in the automotive industry. Based on the microdata of the Relatório Anual de Informações Sociais (Annual Social Information Report), it was decided to analyze the income of workers in the manufacturing sector of automobiles, trucks and utilities and all individuals with formal employment relationship in the two cities in the years 2006 and 2015. About the methodological part, it was chosen to apply the decomposition by differential. The use of this method is very useful to explore the difference of the dependent variable between groups, in this case, wages. Such methodology allows us to decompose this differential between the "explained" and the "not explained" components. Among the main results, it was identified in the automobile sector that if the employees have the same characteristics, the return rate of employees is higher in São Bernardo do Campo when compared to Betim. On the other hand, analyzing the group composed of all the formal workers of the two cities, it was found a different situation, the return of the employees in Betim is bigger than the of employees from São Bernardo do Campo, and this difference has been growing. In this sense, from all the information extracted from this study it is possible to conclude, in a general way, the income inequality between the cities of Betim and São Bernardo do Campo found in the manufacture of automobiles, trucks and utilities sector does not reflect the pattern of salary divergence between those regions.